1984
DOI: 10.1346/ccmn.1984.0320603
|View full text |Cite
|
Sign up to set email alerts
|

Polytypism of Micas. I. MDO Polytypes and Their Derivation

Abstract: Abstract--A procedure leading to the systematic derivation of all maximum-degree-of-order (MDO) polytypes in the three mica families, based on the order-disorder (OD) interpretation of mica structures, has been developed. There are 6 non-equivalent (8 non-congruent) homo-octahedral, 14 (22) mesooctahedral, and 36 (60) hetero-octahedral MDO mica polytypes. The ideal ditrigonalization oftetrahedral sheets leads to a splitting of the polytypes in any mica family into two subfamilies with octahedral and trigonal p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0
1

Year Published

1984
1984
2020
2020

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(6 citation statements)
references
References 18 publications
1
4
0
1
Order By: Relevance
“…MDO polytypes 4-6 have also a common st.~perposition structure with the symbol E.Eu, E,U.U and symmetry H63/mcm. These results are in complete agreement with those obtained by Backhaus and Durovi~ (1984, Figures 5a and 5b) and hold, evidently, also for the meso-and hetero-octahedral families. It is interesting to note that Zvyagin et al (1979, p. 143) also mentioned the existence of two "groups" of mica polytypes, identical with our subfamilies.…”
Section: Compilation Of Classification Tablessupporting
confidence: 92%
“…MDO polytypes 4-6 have also a common st.~perposition structure with the symbol E.Eu, E,U.U and symmetry H63/mcm. These results are in complete agreement with those obtained by Backhaus and Durovi~ (1984, Figures 5a and 5b) and hold, evidently, also for the meso-and hetero-octahedral families. It is interesting to note that Zvyagin et al (1979, p. 143) also mentioned the existence of two "groups" of mica polytypes, identical with our subfamilies.…”
Section: Compilation Of Classification Tablessupporting
confidence: 92%
“…Simulation of the powder XRD pattern indicated that the peak intensity and width of reflections with h = k will be modified to be weaker and larger, respectively, by these stacking faults, and this tendency was actually observed in the experimental XRD patterns (Kogure et al, 2008b). Of course, a single image along one of ± X i is still valid for determining the stacking sequence in micas (and other phyllosilicates), assuming that the mutual rotation between the adjacent layers is restricted to 0°, +120° or –120° (‘subfamily A’) (Backhaus & Ďurovič, 1984), which is indeed the case for most micas.
Fig.
…”
Section: Stacking Sequences In Micasmentioning
confidence: 99%
“…A detailed derivation of MDO structures for the mica families has been given by Backhaus and Ď urovič (1984).…”
Section: Mdo Structuresmentioning
confidence: 99%